Stevia rebaudiana의 항산화 효과 - 정은혜(Eun Hye Jung); 서혜림(Hye Lim Seo); 김민규(Min Gyu Kim); 김영우(Young Woo Kim); 조일제(Il Je Cho) (동의생리병리학회지, 2013)
Stevia rebaudiana is a traditional herb used as a sweetener in Brazil and Paraguay as well as Korea and China. This study investigated the efficacy of Stevia rebaudiana methanol extract (SRE) to protect cells against the mitochondrial dysfunction and apoptosis in hepatocyte. To determine the effects of SRE on oxidative stress, we used the human derived hepatocyte cell line, HepG2 cell. Treatment of arachidonic acid (AA)+iron in HepG2 cells synergistically amplified cytotoxicity, as indicated by the excess reactive oxygen species (ROS) and mitochondrial permeability transition by fluorescence activated cell sorter (FACS) and immunoblot analysis. Treatment with SRE protected hepatocytes from AA+iron-induced cellular toxicity, as shown by alterations in the protein levels related with cell viability such as procaspase-3. SRE also prevented the mitochondrial dysfunction induced by AA+iron, and showed anti-oxidant effects as inhibition of $H_2O_2$ production and GSH depletion. Moreover, we measured the effects of SRE on AMP-activated protein kinase (AMPK), a key regulator in determining cell survival or death. Acetyl-CoA Carboxylase (ACC), a direct downstream target of AMPK. SRE increased phosphorylation of ACC, and prevented the inhibition of ACC phosphorylation by AA+iron. These results indicated that SRE has the ability to protect cells against AA+iron-induced $H_2O_2$ production and mitochondrial impairment, which may be mediated with AMPK-ACC pathway.